2016
DOI: 10.1002/lno.10369
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Chl a content, photosynthesis, and elemental composition in polar and temperate microalgae

Abstract: Polar microalgae live under extreme environmental conditions: permanently low temperatures (−1.7°C to +5°C) and extreme variations in irradiance and day length. These conditions may have led to various specific adaptations allowing Arctic phytoplankton to become specialists under these conditions. The goal of this study is to derive, for polar microalgae, empirical relationships between key physiological parameters (growth rate, photosynthesis–irradiance curve parameters, Chl a : C, and N : C ratios) and growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 79 publications
(148 reference statements)
9
59
0
Order By: Relevance
“…Indeed, the fastest specific growth rate of around 0.65 was found in cells grown in HL at 10°C, and was higher than that previously reported for sea ice diatom communities in situ, as well as the reported maximum growth rates under optimal temperatures (Lacour et al 2017). However, although growth rates were comparable to those of temperate diatom species grown at similar temperatures, they were still much lower than the maximum growth rates of those temperate species (McMinn et al 2005, Coello-Camba et al 2015, Lacour et al 2017. Considering that the water temperature of Saroma Lagoon may rise up to around 20°C in summer, this result suggests that despite being isolated from an ice core, the species we used here can tolerate a wide range of temperatures and can continue its growth throughout the year.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Indeed, the fastest specific growth rate of around 0.65 was found in cells grown in HL at 10°C, and was higher than that previously reported for sea ice diatom communities in situ, as well as the reported maximum growth rates under optimal temperatures (Lacour et al 2017). However, although growth rates were comparable to those of temperate diatom species grown at similar temperatures, they were still much lower than the maximum growth rates of those temperate species (McMinn et al 2005, Coello-Camba et al 2015, Lacour et al 2017. Considering that the water temperature of Saroma Lagoon may rise up to around 20°C in summer, this result suggests that despite being isolated from an ice core, the species we used here can tolerate a wide range of temperatures and can continue its growth throughout the year.…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, the fastest specific growth rate of around 0.65 was found in cells grown in HL at 10°C, and was higher than that previously reported for sea ice diatom communities in situ, as well as the reported maximum growth rates under optimal temperatures (Lacour et al. ). However, although growth rates were comparable to those of temperate diatom species grown at similar temperatures, they were still much lower than the maximum growth rates of those temperate species (McMinn et al.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Indeed, maximum growth rates in the 2−5°C temperature range are on the order of 0.1 per day and then jump to 0.5 per day at 6°C, beyond which growth rates increases as a power function of temperature (Fielding, ). Polar diatoms and other cold‐water adapted phytoplankton have typical growth rates above 0.5 per day in the −1 to 5°C range, thus outcompeting E. huxleyi in cold waters (Lacour, Larivière, & Babin, ). Compared to bottom‐up processes, top‐down control of E. huxleyi blooms is thought to be of limited importance as it has been shown that calcification is an effective strategy to reduce grazer growth by creating indigestion or prolonging digestion time, resulting in net growth of E. huxleyi (Harvey, Bidle, & Johnson, ; Kolb & Strom, ; Monteiro et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies focused solely on the effects of light intensity or temperature on Arctic diatom species (see references in Lacour et al, 2017), a comprehensive understanding of how phytoplankton will respond to changes in the generally strongly N-limited waters of the Arctic can be gained by considering N form as an additional variable. To our knowledge, this study provides the first investigation of the physiological and compositional response of a widespread diatom that qualifies as a long-term resident of the Arctic and a likely survivor of future change.…”
Section: Discussionmentioning
confidence: 99%